McMurdo Dry Valleys LTER: Lake level surveys in the McMurdo Dry Valleys, Antarctica from 1991 to present - McMurdo Dry Valleys LTER; Doran, Peter; Gooseff, Michael (Environmental Data Initiative, 2020)
Manual lake level surveys are conducted each season for several lakes across the McMurdo Dry Valleys of Antarctica. This dataset includes lake levels for Lake Fryxell, Lake Hoare, and Lake Bonney, located in Taylor Valley; Lake Vida, Lake Vanda, and Don Juan Pond, located in Wright Valley; Lake Miers, located in Miers Valley; and Lake House and Lake Joyce, located in Pearse Valley.